2010
DOI: 10.1105/tpc.109.071407
|View full text |Cite
|
Sign up to set email alerts
|

SHORT HYPOCOTYL UNDER BLUE1 Truncations and Mutations Alter Its Association with a Signaling Protein Complex inArabidopsis 

Abstract: Higher plants monitor their ambient light signals through red/far-red absorbing phytochromes and blue/UV-A light absorbing cryptochromes. Subsequent signaling cascades alter gene expression and initiate morphogenic responses. We previously isolated SHORT HYPOCOTYL UNDER BLUE1 (SHB1), a putative transcriptional coactivator in light signaling. SHB1 is homologous to the SYG1 protein family and contains an N-terminal SPX domain and a C-terminal EXS domain. Overaccumulation of the SPX domain caused a long hypocotyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 36 publications
(53 reference statements)
1
33
0
Order By: Relevance
“…Overexpression of SHB1, or just its SPX domain, extends its signalling activity towards a broader spectrum of light wavelengths, suggesting that these signalling activities might be directly modulated by SPX, perhaps by interaction with other domains [31].…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of SHB1, or just its SPX domain, extends its signalling activity towards a broader spectrum of light wavelengths, suggesting that these signalling activities might be directly modulated by SPX, perhaps by interaction with other domains [31].…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
“…However, the SPX domain is required for binding to PHO2, an ubiquitin-conjugating E2 enzyme that helps in the degradation of PHO1 for regulation of phosphate homeostasis [29]. Another SPX-EXS subfamily member is SHB1 (Short Hypocotyl under BLUE1, also known as PHO1;H4) [31].…”
Section: The Association Between Spx Domains and Phosphate Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPX domain of the yeast Syg1 was for long the only evidence of the involvement of the SPX domain in protein interaction, interacting with the b subunit of the G-protein heterotrimer, ultimately suppressing the lethality of the G-protein a-subunit deficiency (Table 1) [11]. Since then, two additional studies, in yeast and Arabidopsis thaliana, have shown a role for the SPX domain in protein interaction [12,13]. In addition, a strong link between proteins harbouring the SPX domain and Pi homeostasis has been observed in yeast and plants.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, recent work in both yeast and plants report that the SPX domain itself could be involved in fine-tuning of Pi transport and signaling, through mechanisms such as physical interactions with other proteins [12,13,21].…”
Section: Introductionmentioning
confidence: 99%